Evidence-based checklist of the Mediterranean Sea fishes - Kovačić, Marcelo; Lipej, Lovrenc; Dulčić, Jakov; Iglesias, Samuel P.; Goren, Menachem (Zootaxa, 2021)
An updated and evidence-based checklist of Mediterranean Sea fishes is provided. Each of the fish species in the Mediterranean Sea listed here was either listed in the last published checklist of the Mediterranean fishes or in other articles, reports or new records, and the checklist is critically assessed. Out of the assessed 791 species previously reported from the Mediterranean, the presence of 759 species is confirmed while 32 species are excluded from the new checklist, by lacking evidence of presence or representing obvious taxonomic confusions. The net increase in known Mediterranean fish species richness since the last checklist is 11%. The non-native Mediterranean species now represent 22.1% (168 species) of the known Mediterranean fish diversity. The evidence-based protocol applied here provides a reliable checklist of marine fishes, for which each of the included species has indeed been recorded at least once within the discussed geographic area in the Mediterranean Sea.